2009
DOI: 10.1208/s12249-008-9184-z
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biodegradable Polyester Poly(Propylene Succinate): Synthesis and Application in the Preparation of Solid Dispersions and Nanoparticles of a Water-Soluble Drug

Abstract: Abstract. Poly(propylene succinate) (PPSu) polymers of average molecular weights from 2,800 to 13,100 g/mol were synthesized and characterized with regard to crystallinity, thermal properties, and cytocompatibility. Higher molecular weight samples exhibited lower degree of crystallinity and melted at lower temperatures. Melting of the polymer appeared to begin at 38°C. PPSu cytocompatibility was investigated based on human umbilical vein endothelial cells viability in the presence of increasing concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 24 publications
4
25
0
1
Order By: Relevance
“…4). Neat PPSu exhibited a melting point at 49°C and a T g value at -27.6°C, in accordance to our previous work [8]. The addition of MAL-PEG into PPSu reduced the melting point of PPSu to 35.6°C due to cocrystallization with PEG, as was verified by the XRD studies, while a second melting point appeared at 47.4°C.…”
Section: Chemical Structure and Characterization Of Functional Materialssupporting
confidence: 90%
See 1 more Smart Citation
“…4). Neat PPSu exhibited a melting point at 49°C and a T g value at -27.6°C, in accordance to our previous work [8]. The addition of MAL-PEG into PPSu reduced the melting point of PPSu to 35.6°C due to cocrystallization with PEG, as was verified by the XRD studies, while a second melting point appeared at 47.4°C.…”
Section: Chemical Structure and Characterization Of Functional Materialssupporting
confidence: 90%
“…Although these polyesters are widely used as drug carriers and implants, their low degradation rate [6] sparked an increased interest for the synthesis of new materials with innovative and enhanced properties. Poly(propylene succinate) (PPSu) is such a new biocompatible polyester with relatively high biodegradation rate due to its low degree of crystallinity [7,8]. Furthermore, due to its low melting point (T m = 44°C), which is close to the physiological body temperature [9,10], PPSu could be used as drug nanocarrier appropriate for selective drug release at the tumor site using local hyperthermia.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the pellets have been prepared at 145 C (above the melting temperature), dried under vacuum at 100 C (above the crystallization temperature), and cooled very slowly inside the vacuum oven down to room temperature, so that the crystallization temperature region was crossed at rates <1 C min 21 . The crystallization was thus complete, as the article by Bikiaris et al [12] stated that PBS crystallizes rapidly on cooling from the melt, which is confirmed by our thermogram shown below in Figure 2. Furthermore, the TSDC experiments covered the temperature interval between 2130 and 25 C, well below the crystallization temperature.…”
Section: Tsdc and Tspcsupporting
confidence: 86%
“…Semicrystalline carriers that have been applied in the formulation of pharmaceutical solid dispersions so far are PEG and its surface active derivatives such as poloxamer [58,59], gelucire [60,61] as well as some less commonly used polymers including chitosan and [62] poly(propylene succinate) [63]. These carriers contain both crystalline and amorphous domains, the proportions of which depend on the molecular weight of the carrier and the sample preparation conditions.…”
Section: Semicrystalline Carriermentioning
confidence: 99%